2006
DOI: 10.1200/jco.2006.08.2073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways in Invasive Bladder Cancer: New Insights Into Mechanisms, Progression, and Target Identification

Abstract: Papillary and invasive cancers of the urinary bladder appear to evolve and progress through distinct molecular pathways. Invasion in bladder cancer forebodes a graver prognosis, and these tumors are generally characterized by alterations in the p53 and retinoblastoma (RB) pathways that normally regulate the cell cycle by interacting with the Ras-mitogen activated protein kinase signal transduction pathway. Tumor angiogenesis further contributes to the neoplastic growth by providing a constant supply of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
198
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(214 citation statements)
references
References 125 publications
5
198
1
10
Order By: Relevance
“…73,74 Deep genomic profiling with a comprehensive NGSbased diagnostic assay of metastatic UC identified an unexpectedly high frequency of potentially actionable GAs that can both influence therapy selection and direct patients to enter clinical trials using targeted therapies. Moreover, these opportunities for UC patients to receive targeted therapies include both commercially available agents approved for other indications and drugs in both early and late stages of clinical development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…73,74 Deep genomic profiling with a comprehensive NGSbased diagnostic assay of metastatic UC identified an unexpectedly high frequency of potentially actionable GAs that can both influence therapy selection and direct patients to enter clinical trials using targeted therapies. Moreover, these opportunities for UC patients to receive targeted therapies include both commercially available agents approved for other indications and drugs in both early and late stages of clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Characterization of the genomic drivers of UC development and progression has long been of interest to cancer biologists, urologists, genitourinary oncologists and pathologists. [16][17][18][19][20] Protein expression studies mostly performed on formalinfixed, paraffin-embedded (FFPE) specimens using immunohistochemistry (IHC) have been widely used to predict prognosis. [16][17][18][19][20] Increased DNA copy number determined by fluorescence in situ hybridization (FISH) has been used for both early UC detection 21,22 and prediction of prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that there are numerous reproducible molecular abnormalities that occur during the development and progression of urothelial carcinoma. 3,23,24 When normal urothelium undergoes mutations of chromosome 9p and fibroblast growth factor receptor 3, this may lead to the development of urothelial hyperplasia or low-grade papillary urothelial carcinoma. 3 Up to 70% of low-grade tumors recur, however they may Numerous studies have shown that high-grade urothelial carcinoma and in situ urothelial carcinoma show genetic alterations that are distinct from those seen in their low-grade counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomy of chromosomes 3, 7 and 17 are associated with high-grade urothelial carcinoma and deletions of chromosome 9p21 (where the p16INK4a tumor suppressor gene resides) are seen in up to 60% of superficial lowgrade, papillary tumors. [22][23][24] Although Urovysiont FISH was initially approved for use in urine samples, it can also be applied to paraffin-embedded tissues.…”
mentioning
confidence: 99%